TRANSMISSION ION CHANNELING IMAGES OF CRYSTAL DEFECTS - King, P; Breese, M; Wilshaw, P; Smulders, P; Grime, G (1995)
This paper demonstrates how images of crystal defects can be produced using ion channeling. A focused, scanned beam of MeV protons from the University of Oxford Nuclear Microprobe has been used. With the beam aligned with a channeling direction of the crystal, protons transmitted through the thinned samples are detected and images produced showing the mean transmitted proton energy loss. Regions where dechanneling is occurring owing to the presence of a defect are revealed. Images of groups of misfit dislocations in epitaxial Si1-xGex on Si provide evidence of the lattice plane rotation produced by these defects. Stacking faults have also been imaged, and the choice of the planar channeling direction enables information on the fault translation vector to be obtained.